ChemInform Abstract: Base‐Catalyzed Asymmetric α‐Functionalization of 2‐(Cyanomethyl)azaarene N‐Oxides Leading to Quaternary Stereocenters. Issue 34 (4th August 2016) - Izquierdo, Joseba; Landa, Aitor; Bastida, Inaki; Lopez, Rosa; Oiarbide, Mikel; Palomo, Claudio
Abstract: A highly enantioselective α‐functionalization of 2‐(cyanomethyl)pyridine N‐oxides and pyrazine N‐oxides via conjugate addition of 4‐hydroxy‐4‐methylpent‐1‐en‐3‐one or α‐amination with di(tert‐butyl) or dibenzyl azodicarboxylate is developed.